Significance of emotional work-home spillover and harsh parenting during the Covid-19 pandemic - Angelica, Celine; Pristinella, Debri (International Journal of Research in Counseling and Education, 2021)
The objective of this research is to find out whether positive and negative emotions transmitted from work while taking care of their children and assisting them during home-based learning, has any influence on parents’ harsh parenting towards children. Data was collected using JAWS and CTSPC instruments and received responses of 49 parents aged 20-59 years old, with children’s education level ranging from kindergarten to senior high school. The Data were analyzed using Spearman Correlation. The findings show no significant relationship between positive emotion and harsh parenting, as well as between negative emotion and harsh parenting. Several factors such as parents’ age, family economy, and children’s level of education may influence the findings, although the specific influence of these factors needs further research.